HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG HIPERTENSI DALAM KEHAMILAN TERHADAP RESIKO PREEKLAMSIA BERAT - Ester Simanullang (STIKes Mitra Husada Medan, 2019)
Hypertension is the increase in systolic blood pressure above 140 mmHg and diastolic above 90 mmHg. Hypertension often causes changes in blood vessels that can lead to increasing blood pressure. Today people prefer to choose ready meals are generally very low in fiber, high in fat and salt mengandum lost. The public should be aware that taking makanana above can lead to hypertension. So for people who have suffered or are expected to organize their daily diet. Regulate diet but to draw up the frequency of food consumption, food habits, consumption of drinks, the portion size and qulity of food daily. Research aims to determine the aattitude of the attitude of the mother of hypertension on the incidence of pre-eclampsia. The study design was descriptive. Respondents in this study were pregnant women who have hypertension and pre-eclampsia in the People’s Health Center Island Asahan number of 30 respondents. Sampling of this research is total sampling. Collecting data in this study using a questionnaire designed by researcher and distributed to the respondents. Whereas the data analysis using Chi-square statistical test with a cinfidence level of 95% (α = 0,05). The results showed no relationship between knowledge and attitude of pregnant women about hypertension on the incidence of pre-eclampsia with a value of 0.001 (<0.05). Keywords : Knowledge attitude, hypertension and pre-eclampsia